Evaluation of multiple retailers’ market positions on the basis of image attributes measurement - Urbonavičius, Sigitas; Ivanauskas, Robertas (Journal of Business Economics and Management, 2005)
Intense competition in retailing sector requires searching for new and more effective tools of competing with rivals. One of the possible ways seems to go through applying positioning concept in retailing. Positioning in retailing refers to strategy for development of a desirable image, which would help to differentiate a retail company and move away from direct price competition. Besides that, image management provides possibilities for increasing customer perceived value and/or increasing prices. The paper presents methodology for establishing multiple retailers’ positions. This methodology is based on evaluation of image attributes’ importance for customers. Factor analysis allows revealing more general latent factors that are used to evaluate retailers’ positions in a perceptual space. This allows drawing conclusions on how much Lithuanian multiple retailers are similar or differentiated from the standpoint of their customers. First published online: 14 Oct 2010